Chronic Septic Granulomatosis Revealed in Adulthood by Respiratory Manifestations - Haouassia, Fatima Ezzahra; Chaanoun, Khadija; Zaghba, Nahid; Benjelloun, Hanane; Yassine, Najiba (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
Chronic septic granulomatosis is a rare genetic disease that affects the immune system. It is characterized by a primary immune deficiency that makes it more difficult for phagocytic cells (such as polymorphonuclear neutrophils, eosinophils, monocytes, and macrophages) to eradicate some harmful bacteria and fungi. It is considered an orphan disease because it affects less than 0.05% of a given population.